Effects of 8-Week Functional vs. Traditional Training on Athletic Performance and Functional Movement on Prepubertal Tennis Players - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2019)
Yildiz, S, Pinar, S, and Gelen, E. Effects of 8-week functional vs. traditional training on athletic performance and functional movement on prepubertal tennis players. J Strength Cond Res 33(3): 651-661, 2019-In recent years, studies on functional training (FT) have gained importance among older adults and health care services, but there is a lack of research on the athletic performance of children. Fundamental movement skills are basic skills that need to be improved by the age of 10, and these skills are fundamental to every sport. While developing these basic movement skills, some athletic abilities of children should not be neglected and will be a basis for the future. In this way, children will have the ability to perform their sport-specific movement skills easily when the age of specialization comes. Our hypothesis is that increased functional movement will enhance athletic performance of child tennis players. Question of the study is will increased functional movement enhance athletic performance of child tennis players? The purpose of this study is to investigate the effects of the FT model on the athletic performance of young athletes. This study included 28 young tennis players (mean age: 9.6 +/- 0.7, height: 134.1 +/- 6.8, body mass: 31.3 +/- 4.1, and fitness age: 3.1 +/- 1.1) who have an 80% or more dominant side based on the lateralization test and a functional movement screen (FMS) score below 75%. Ten subjects were included in each of the FT group (FTG) and the traditional training group (TTG), 8 subjects were included in the control group (CG). The training program was implemented on 3 nonconsecutive days in a week for 8 weeks. All subjects performed CG exercises; FTG performed additional exercises based on the FT model, and TTG performed additional exercises based on the TT model. Flexibility, vertical jump, acceleration, agility, balance, and FMS tests were conducted before the training program, at the end of the fourth and the eighth week. The Friedman test analysis method bearing intragroup repeated measurements was used to evaluate the effects of the training program on the dependent variables among weeks (beginning the fourth week and the eighth week) since groups display distribution in nonparametric order. The differences between the averages were tested with Wilcoxon post hoc analyses. The Kruskal-Wallis Test analyses method was used to evaluate the effects of the training program on dependent variables among the groups (CG, TTG, and FTG). The differences between the averages were tested with Mann-Whitney U post hoc analyses. Intraclass correlation coefficient (ICC) values were calculated to determine the test-retest reliability of all measurements. According to the data, there was no difference in performance measurements between CG, TTG, and FTG before the exercise program (p > 0.05), but the differences between the groups were significant (p < 0.01) after 4 weeks and 8 weeks. A significant decrease was found in FMS score in CG (p < 0.01), while no difference was found in other parameters (p > 0.05). In TTG, FMS score significantly decreased (p < 0.01), dynamic right balance (p < 0.01) and dynamic left balance (p < 0.05) increased. But, no statistically significant difference was found in other parameters (p > 0.05) in TTG. In FTG, all parameters improved, and differences were statistically significant (p <= 0.001). Based on these results, the FT model seems to be more effective than the TT model in terms of increasing athletic performance.
Keywords: FMS; functional training; muscular imbalance; unitlateral loading; MUSCLE STRENGTH; CEREBRAL-PALSY; MUSCULAR FITNESS; INJURY; BALANCE; PROGRAM; INTERVENTION; CHILDREN; ABILITY; WOMEN